Bigiswun Kid Project: a longitudinal study of adolescents living with high rates of prenatal alcohol exposure, fetal alcohol spectrum disorder and early life trauma in remote Australian Aboriginal communities. Issue 4 (1st April 2022) - Rice, Lauren J; Tsang, Tracey W; Carter, Emily; Hand, Marmingee; Davies, Jadnah; Thomas, Sue; Bedford, Eric; Bear, Emma; Carter, Cheyenne; Cannon, Lisa; Elliott, Elizabeth J
Abstract : Introduction: The Lililwan Project was the first Australian population-based prevalence study of fetal alcohol spectrum disorder (FASD) using active case ascertainment. Conducted in 2010–2011, the study included 95% of all eligible children aged 7–9 years living in the very remote Aboriginal communities of the Fitzroy Valley, Western Australia. Women from Marninwarntikura Women's Resource Centre, a local Aboriginal-led organisation, are concerned that some participants from the study are struggling in adolescence so partnered with researchers from the University of Sydney to follow up the Lililwan cohort in 2020–2022 at age 17–19 years. The overarching aim of the Bigiswun Kid Project is to identify adolescents' needs and build knowledge to inform services to improve the health and well-being of adolescents in remote Aboriginal communities. The specific aims are to: (1) provide a voice to adolescents and their families to understand the health and well-being status of the Lililwan cohort at 17–19 years. (2) Examine relationships between exposures during pregnancy, birth characteristics, and health and neurodevelopment at 7–9 years, and positive/adverse adolescent outcomes at 17–19 years. This information will identify prenatal and early life factors that predict good health and well-being in adolescence. (3) Determine whether management plans provided in the Lililwan Project were followed, and identify past and present service gaps, support needs and barriers to service use. (4) Determine if key physical characteristics of FASD change between childhood and adolescence in this Aboriginal population. Ethics and dissemination: Approved by the Kimberley Aboriginal Health Planning Forum and relevant ethics committees.